2020
DOI: 10.1111/ecc.13385
|View full text |Cite
|
Sign up to set email alerts
|

Living with cancer in the COVID‐19 pandemic: An Italian survey on self‐isolation at home

Abstract: Objective To investigate the perception of self‐isolation at home in patients with cancer during the lockdown period resulting from the COVID‐19 outbreak in Italy. Methods A cross‐sectional descriptive study was conducted through an online survey of patients with cancer who were sheltering at home from 29th March to 3rd May 2020. Perception of self‐isolation was assessed using the ISOLA scale, after evaluation of its psychometric properties. Content analysis was used to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
2
20
0
3
Order By: Relevance
“…Previous research suggests that while both patients and ICs experience loneliness during COVID-19 [15,29,30], some patients expressed feelings of societal connectedness because everybody was advised to stay home [15]. This finding is consistent with our subthemes "changes in societal behaviors" and "cancer experience as a resource."…”
Section: Discussionsupporting
confidence: 81%
“…Previous research suggests that while both patients and ICs experience loneliness during COVID-19 [15,29,30], some patients expressed feelings of societal connectedness because everybody was advised to stay home [15]. This finding is consistent with our subthemes "changes in societal behaviors" and "cancer experience as a resource."…”
Section: Discussionsupporting
confidence: 81%
“…Studies show that patients with pre-existing NCDs have found it difficult to maintain a healthy lifestyle during the COVID-19 pandemic and associated lockdown measures introduced by countries 227 . Patients with coronary heart disease [228][229][230][231][232] , neurological disorders 233,234 , diabetes 235,236 and cancer 237,238 have had to compromise on their physical activity routine, dietary patterns, and social connectedness in particular 227,236,239,240 as did families with children who had chronic respiratory diseases 193,241 . Poor glycemic control in diabetics due to altered lifestyle was reported in many studies [242][243][244][245][246][247][248] , while one study in India reported an improvement in the glycemic status of patients with type II diabetes mellitus 249 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 99%
“…During the COVID-19 pandemic, many people have been, indeed, experiencing anxiety, depression, panic, as well as economic-financial problems, such as unemployment, increased poverty, and declining incomes and earnings [14][15][16], that have affected people's sexual activity [17]. Restrictions on people's activities, reduced sports activities, economic issues, increased psychological stress, and reduced entertainment have dramatically impacted sexual activity and functioning [18].…”
Section: Introductionmentioning
confidence: 99%